Effect of Either Powder or Encapsulated Form of Garlic and Phyllanthus niruri L. Mixture on Broiler Performances, Intestinal Characteristics and Intestinal Microflora - Natsir , M.H.; Hartutik,; Sjofjan, O.; Widodo, E. (International Journal of Poultry Science, 2013)
Effect of the mixture of garlic and Phyllanthus niruri L. in either powder or encapsulated form on broiler performances, intestinal characteristics and intestinal microflora were investigated. One hundred ninety two 1-day-old Lohmann broiler chicks were subjected to 8 different dietary groups, namely 2 forms of phytobiotic (non-encapsulated powder and encapsulated) and 4 levels of inclusion (0, 0.4, 0.8 and 1.2%). Data were then analyzed by two-way Nested of Completely Randomized Design ANOVA and if there was significant effect followed by Duncan’s Multiple Range Test. The results showed that combination of garlic and Phyllanthus niruri L. in encapsulated form improved (P